Electric Machinery and Transformers - Guru, Bhag S.; Hiziroglu, Huseyin R. (New York ; Oxford : Oxford University Press, 2000)
This text is designed for courses in electrical engineering. It discusses the principles behind building the primary infrastructure for the generation of electricity that supplies the energy needs of people throughout the world.
Previous ed.: New York: Academis, 1988.
Includes bibliographical references and index.
Keywords: Electric machinery; Technology